KONDISI PERSONAL HYGIENE DAN SANITASI PABRIK TAHU DI SENTRA INDUSTRI TAHU KAMPUNG KRAJAN MOJOSONGO SURAKARTA DAN PENGARUHNYA TERHADAP HYGIENITAS TAHU YANG DIPRODUKSI - CICIK SUDARYANTININGSIH; YONATHAN SURYO PAMBUDI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Almost all family in Indonesia got tofu as a regular menu. Tofu have a good amount of nutrition that good for health. Therefor tofu must meet food worthiness and food safety. Food worthiness is a condition when food doesn’t dammaged, rotten dirty or decomposed. Food safety is an effort to prevent food from biology contamination, chemist contamination or any other factor that threaten human health. This contamination came from less good factory sanitation or tofu artisan with less personal hygiene. Purpose of this study 1). Identify the personal hygiene of tofu artisan in Krajan Mojosongo Surakarta. 2) Identify the sanitation of tofu factory in Krajan Mojosongo Surakarta. 3) Describe the effect of personal hygiene on the tofu produced. 4) Describe the sanitation of tofu factory on the tofu produced. Method This is an experimental, with three. Step one and two, with quesionaire, to gather information about personal hygiene and sanitation of tofu factory. Step three, simple experiment to compare tofu freshness between tofu artisan with good personal hygiene and less good personal hygiene, and comparing between tofu factory with good sanitation and less good sanitation. The conclusions of this research are: 1) From the process of making and packaging tofu in the tofu industry center, Krajan village, Mojosongo, Surakarta, there are 36 percent (%) respondents who know tofu craftsmen have or practice good personal hygiene and the remaining 64 percent (%) do not. or have not implemented good personal hygiene; 2) The sanitation of the tofu factory in Krajan Mojosongo Surakarta is known to be 33 percent (%) in good condition, while 40 percent (%) is classified as adequate, and the remaining 27 percent (%) is in poor condition; 3) Tofu produced by craftsmen with good personal hygiene can last up to three (3) days of freshness, while tofu produced by craftsmen with poor personal hygiene in two (2) days has suffered physical damage; 4) Tofu that is produced in factories with good sanitation, the freshness can last up to three (3) days. Meanwhile, tofu that is produced by factories with poor sanitation in two (2) days has suffered physical damage.